The Influence of Financial Management Practices on Company Performance: Analysis of Cash Flow, Debt, Working Capital, and Capital Structure - Feriandy, Feriandy (International Journal of Business and Applied Economics, 2024)
This research explores the relationship between financial management practices and corporate performance. It aims to analyze how key components such as cash management, debt management, working capital management, and capital structure impact the financial outcomes of firms, using performance indicators like Return on Assets (ROA) and Return on Equity (ROE). The study highlights the importance of efficient cash flow management, strategic debt usage, and optimized working capital in driving profitability and stability. Additionally, the research identifies how technology, particularly financial management software and big data analytics, plays a pivotal role in enhancing decision-making processes. The findings suggest that companies adopting a balanced approach to financial management, coupled with technological advancements, experience better financial performance and long-term sustainability. This paper provides actionable insights for business managers, financial analysts, and policymakers aiming to improve financial management strategies.